2001
DOI: 10.1111/j.1939-1676.2001.tb02329.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Bactericidal/Permeability‐Increasing Protein (rBPI21) for Treatment of Parvovirus Enteritis: A Randomized, Double‐Blinded, Placebo‐Controlled Trial

Abstract: We evaluated the ability of an antimicrobial and endotoxin-neutralizing agent, the recombinant amino terminal fragment of bactericidal permeability-increasing protein (rBPI 21 ), to decrease plasma endotoxin concentration and severity of clinical signs of canine parvovirus and to improve survival. This randomized, double-blinded, placebo-controlled clinical trial included 40 client-owned dogs and 9 normal puppies from a closed research colony. Dogs weighing Ͼ5 kg (11 lb) with fecal antigen-confirmed parvovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
0
6
1
1
Order By: Relevance
“…Canine parvovirus disease is extremely contagious, causing considerable morbidity and mortality in young canines (Prittie, 2004;Greene and Decaro, 2012) with reported mortality rates exceeding 90% for young nonimmune animals (Bragg et al, 2012). An estimated one million dogs are infected annually in the United States alone, despite the widespread availability and use of vaccines (Otto et al, 2001). The virus first emerged in the United States during a nationwide outbreak in the fall of 1978 (Appel et al, 1980) and within two years the disease became established worldwide (Prittie, 2004;Greene and Decaro, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Canine parvovirus disease is extremely contagious, causing considerable morbidity and mortality in young canines (Prittie, 2004;Greene and Decaro, 2012) with reported mortality rates exceeding 90% for young nonimmune animals (Bragg et al, 2012). An estimated one million dogs are infected annually in the United States alone, despite the widespread availability and use of vaccines (Otto et al, 2001). The virus first emerged in the United States during a nationwide outbreak in the fall of 1978 (Appel et al, 1980) and within two years the disease became established worldwide (Prittie, 2004;Greene and Decaro, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Canine parvovirus (CPV), a highly contagious virus that attacks rapidly dividing cells, is a significant cause of morbidity and mortality in young domestic dogs 1‐3 . Reported mortality rates range from 4% to 48% with supportive care and as high as 91% in untreated experimentally infected dogs 2,4‐7 . While there is an effective vaccine available, the disease still persists.…”
Section: Introductionmentioning
confidence: 99%
“…Release of free lipopolysaccharide is a potent stimulator of sepsis, so rBPI21 binding prevents lipopolysaccharides from interacting with host cells, reducing the septic response. Although shown to be beneficial when used in humans with meningococcal sepsis (Levin et al, 2000), the only veterinary study on rBPI21 use on dogs with CPV enteritis reported no benefit (Otto et al, 2001).…”
Section: Treatmentmentioning
confidence: 99%
“…Since the virus was first discovered in 1978 it has evolved and there are now three known strains that can cause enteritis; CPV‐2a, b and c. In experimentally infected dogs, mortality without treatment is as high as 91% (Prittie, 2004). Although no definitive treatment has been reported, survival rates with intensive therapy can be up to 90%; however, survival rates in tertiary, referral hospitals have been shown to be higher than those in first opinion practice (Otto et al, 2001). This article will cover the pathophysiology of CPV infection and discuss the current and experimental treatments available.…”
mentioning
confidence: 99%